Green Building in Russia as well as its problems and solutions - Nikolai Tuzov (Недвижимость: экономика, управление, 2021)
The article deals with the issues of environmental (“green”) construction in Russia in relation to the tasks of low-rise and individual development. The article describes the history of the formation of the ecological construction market in Russia and abroad, gives a general classification and the main directions of its development. The ad-vantages of green construction, the problems that hinder the rapid development of ecological construction and the stimulating factors of such development are described. The applicable standards of green construction are indicated, both established by the state in the form of normative legal acts, and voluntary, and the advantages of following environmental standards are shown. Practical examples of ecological construction and problems faced by developers in practice are given. The concepts of Passive House, energy-efficient house and non-volatile house are considered in detail, indicating the ways to use the elements of such concepts in the implementation of real construction at the moment, including some practical examples of technical and technological solutions, as well as ways to further improve them. Examples of low-rise buildings currently under construction using standards and principles of ecological construction are given. The Russian standards of green construction are considered in de-tail, with references to specific regulations and other sources regulating the issues of ecological construction, and the ways of their further development and improvement are indicated. A mathematical model of the order of construction of eco-mobility facilities is proposed, where the capital return indicator is selected as an important criterion, which is determined taking into account the different times of costs for the objects being introduced. Its maximization leads to the choice of such an option, which will be characterized by the largest intermediate volume of input objects, as well as the smallest amount of reduced capital investments, i.e. their more rational dynamics. Thus, this indicator characterizes the efficiency of using capital investments, as well as their return as a result of reducing construction in progress.